Mengeš in the Roman Period - Sagadin, Milan; Josipovič, Draško; Meterc, Janez (Arheološki vestnik, 1995)
The article discusses three rescue excavations in the region of Mengeš: in the courtyard of the Semesadika firm (1978), at the building site of the kindergarten (1985/86), and at the building site of a sports hall (1988). The first two sites offered traces of six structures, most probably residential, some kind of semi-underground buildings (tugurium). The accompanying small finds indicate an unusually broad chronological span from the 1st to the 6th or even 7th centuries AD. This phenomenon is insufficiently explained (the intrusion of later structures into earlier cultural strata, flooding, mechanical removal of upper layers?). The building site of the sports hall in 1988 resulted in a cultural stratum up to 3 meters thick, with the small finds primarily encompassing the first two centuries AD. The pottery remains indicate a distinct difference between the imported vessels and the local coarse ware that was predominant. Remains from metallurgical activities were also discovered (slag, fragments of furnace coatings). These sites characterize the problem of distinguishing the degree of Romanization in individual sections of this non-urban region.